Perceptions of Artificial Intelligence among Philippine Undergraduate Students: Examining Instrument Construct and Demographic Influences on Knowledge and Beliefs - Hortelano, Julius Ceasar; Salamia, Shella (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
Artificial Intelligence (AI) is ubiquitous, yet the perceptions of Filipino undergraduate students (UGS) remain limited. Using an explanatory sequential mixed methods design, we surveyed 537 UGS to examine their knowledge and beliefs about AI in higher education. An adapted instrument was first validated through exploratory factor analysis, revealing a three-factor structure: perceived threat to human autonomy and employment, perceived academic and economic utility, and perceived negative consequences and risks. Students reported moderate self-rated knowledge (M = 6.51, SD = 2.18). Beliefs were largely neutral to positive, with no significant demographic differences. However, knowledge varied significantly: males scored higher than females (U = 30,244, p = .01), students aged 21–25 outperformed those under 20 (H(2) = 13.85, p < .001), IT students exceeded agriculture majors (H(6) = 13.29, p = .04), and third-years surpassed first-years (H(3) = 9.87, p = .02). Qualitative responses emphasized AI’s role in learning support, accessibility, and interaction, while concerns focused on over-reliance, reduced human relationships, and misinformation. Interpreted through the Technology Acceptance Model, the Unified Theory of Acceptance and Use of Technology, and Critical Pedagogy, the findings inform Philippine higher education in shaping curriculum, faculty development, and governance for responsible AI integration.